Analysis the Impact of Halal Certification Strategies on the Development of Small and Medium Enterprises (SMESs) in Bandung - Kurniawan, Fakhry Hafiyyan; Cupian, Cupian; Faisal, Yudi Ahmad; Nugraha, Ilham (IAIN Manado, 2024)
The study aims to determine the strategy for halal certification in the development of Culinary SMEs in the Greater Bandung Region from an internal and external perspective. The research method used is a qualitative method with a SWOT matrix approach of IFAS (Internal Strategic Factors Analysis Summary) and EFAS (External Strategic Factors Analysis Summary) and AHP (Analytical Hierarchy Process). The population in this study are competent parties who know the strategy of halal certification in the development of SMEs in the Greater Bandung Region and sampling was carried out using a purposive sampling technique with a total sample of 18 expert respondents who are ready and willing to be respondents. Based on the results of the IFAS and EFAS assessments, the halal certification strategy is in quadrant I, namely,